Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.2134/agronj2003.3290
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Oleic Acid Content in Sunflower Oil

Abstract: Knowledge of the effects of temperature and geographic variables on the oleic acid content of sunflower (Helianthus annuus L.) oil allows us to predict the type of oil that will be produced in a particular area. This study was designed to establish a simple empirical model, which uses available variables of previously established effects, to estimate the final oleic acid composition of sunflower oil. Over two growing seasons, sunflower seeds were collected from Spain's main producing areas, and the oleic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The increase in oleic acid from north to south latitude and the corresponding reverse trend in linoleic acid has been reported by Robertson et al (1978) The same authors found that latitude had limited effect on saturated fatty acid concentration in sunflower oil. Similar results on the effect of climatic conditions and latitude on linoleic acid were reported by Lajara et al (1990) Sobrino et al (2003) developed models to explain and predict oleic acid concentration in sunflower oil as a function of geographic and climatic conditions. They reported temperature during development and maturation of sunflower achenes is one of the most important factors for production of oleic acid.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The increase in oleic acid from north to south latitude and the corresponding reverse trend in linoleic acid has been reported by Robertson et al (1978) The same authors found that latitude had limited effect on saturated fatty acid concentration in sunflower oil. Similar results on the effect of climatic conditions and latitude on linoleic acid were reported by Lajara et al (1990) Sobrino et al (2003) developed models to explain and predict oleic acid concentration in sunflower oil as a function of geographic and climatic conditions. They reported temperature during development and maturation of sunflower achenes is one of the most important factors for production of oleic acid.…”
Section: Resultssupporting
confidence: 73%
“…The fatty acid composition of vegetable oils influences their functional and nutritional properties (Warner et al, 2003; Burton et al, 2004) and determines their uses. The fatty acid composition of sunflower oil depends on genetic and environmental conditions (Robertson et al, 1978; Lajara et al, 1990; Miller and Vick, 1999; Sobrino et al, 2003). Sunflower seed contain up to 90% unsaturated fatty acids (combined oleic and linoleic), and approximately 10% saturated fatty acids (palmitic and stearic) (Steer and Seiler, 1990).…”
mentioning
confidence: 99%
“…Reducing the TSFA in sunflower oil would improve its dietary properties, would result in higher oxidative stability, and may benefit both consumers and producers (Miller and Vick, 1999; Flagella et al, 2002). Previous research has demonstrated that FA composition of sunflower oil may be affected by genetic (Miller and Vick, 1999; Burton et al, 2004; Izquierdo and Aguirrezábal, 2008; Skoric et al, 2008) and environmental conditions (Robertson et al, 1978; Lajara et al, 1990; Steer and Seiler, 1990; Flagella et al, 2002; Sobrino et al, 2003; Izquierdo and Aguirrezábal, 2008; Zheljazkov et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…T he environment affects fatty acid composition in the oil of traditional sunflower hybrids. The increase in the oleic/linoleic acid ratio with increasing temperature during grain filling has been widely reported (Canvin, 1965; Nagao and Yamazaki, 1984; Sobrino et al, 2003). Prediction of fatty acid composition using temperature at different periods of grain filling has been attempted in a few studies.…”
mentioning
confidence: 95%